A single regulatory gene is sufficient to alter Vibrio aestuarianus pathogenicity in oysters. (27th January 2015) - Goudenège, David; Travers, Marie Agnès; Lemire, Astrid; Petton, Bruno; Haffner, Philippe; Labreuche, Yannick; Tourbiez, Delphine; Mangenot, Sophie; Calteau, Alexandra; Mazel, Didier; Nicolas, Jean Louis; Jacq, Annick; et al.
Summary: Oyster diseases caused by pathogenic vibrios pose a major challenge to the sustainability of oyster farming. In France, since 2012 a disease affecting specifically adult oysters has been associated with the presence of V ibrio aestuarianus. Here, by combining genome comparison, phylogenetic analyses and high‐throughput infections of strains isolated before or during the recent outbreaks, we show that virulent strains cluster into two V . aestuarianus lineages independently of the sampling dates. The bacterial lethal dose was not different between strains isolated before or after 2012. Hence, the emergence of a new highly virulent clonal strain is unlikely. Each lineage comprises nearly identical strains, the majority of them being virulent, suggesting that within these phylogenetically coherent virulent lineages a few strains have lost their pathogenicity. Comparative genomics allowed the identification of a single frameshift in a non‐virulent strain. This mutation affects the varS gene that codes for a signal transduction histidine‐protein kinase. Genetic analyses confirmed that varS is necessary for infection of oysters and for a secreted metalloprotease expression. For the first time in a V ibrio species, we show here that VarS is a key factor of pathogenicity.